Experiences of health service access: A qualitative interview study of people living with Parkinson's disease in Ireland - Emma O' Shea; Aphie Rukundo; Geraldine Foley; Tony Wilkinson; Suzanne Timmons (Wiley, 2024)
Abstract Background People with Parkinson's disease (PD) do not always access specialist outpatient services in a timely manner in Ireland. The perspectives of people living with PD, relating to service access, are largely absent in the existing literature. Aim To explore experiences of PD service access for people living with PD, using a qualitative approach. Methods Purposive maximum variation sampling was used. Semi‐structured telephone interviews were conducted with 25 service users, including people with PD (n = 22) and supporting carers (n = 3). Informed consent was obtained from all participants. Interviews ranged in duration from 30 to 90 min. Data were managed in NVivo 12 and interpreted inductively using thematic analysis. The researchers were reflexive throughout the research process. The Consolidated Criteria for Reporting Qualitative Research checklist was employed to maximise transparency. Results The findings highlight several key barriers to and facilitators of equitable and timely service access. Three key themes were identified comprising experiences of PD service access including 'geographical inequity', 'discriminatory practices', and 'public and private system deficits'. Together, these themes illustrate how a two‐tiered and under‐resourced health system lacks capacity, in terms of infrastructure and workforce, to meet PD needs for both public and private patients in Ireland. Conclusions These findings point to problems for PD care, relating to (i) how the health system is structured, (ii) the under‐provision and under‐resourcing of specialist outpatient PD services, including medical, nursing, and multidisciplinary posts, and (iii) insufficient PD awareness education and training across health settings. The findings also show that telemedicine can provide opportunities for making access to certain aspects of PD care more flexible and equitable, but the feasibility and acceptability of technology‐enabled care must be assessed on an individual basis. Implications for policy, practice and research are discussed. Patient or Public Contribution The design and conduct of this study were supported by an expert advisory group (EAG) of 10 co‐researchers living with PD. The EAG reviewed the interview schedule and the protocol for this study and provided detailed feedback from their perspective, to improve the methods, including the interview approach. The group also reviewed the findings of the study and contributed their insights on the meaning of the findings, which fed into this paper.